2009
DOI: 10.1111/j.1365-2788.2009.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause‐specific mortality and death certificate reporting in adults with moderate to profound intellectual disability

Abstract: Strategies to reduce inequalities in people with ID need to focus on decreasing mortality from potentially preventable causes, such as respiratory infections, circulatory system diseases and accidental deaths. The lack of mention of ID on death certificates highlights the importance of effective record linkage and ID reporting in health and social care settings to facilitate the government's confidential inquiry into causes of death in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 12 publications
4
104
3
Order By: Relevance
“…Although some studies have found an increase in prevalence of CVD 83 or CVD mortality 279 in individuals with ID, other studies report no difference or reduced risk compared with the general population (see Chapter 2, Results). Lower CVD mortality than in the general population could partially be explained through competing risks, given that individuals with ID have higher mortality from other causes, particularly respiratory illnesses, congenital abnormalities, neurological disorders and accidental injury.…”
Section: Economic Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Although some studies have found an increase in prevalence of CVD 83 or CVD mortality 279 in individuals with ID, other studies report no difference or reduced risk compared with the general population (see Chapter 2, Results). Lower CVD mortality than in the general population could partially be explained through competing risks, given that individuals with ID have higher mortality from other causes, particularly respiratory illnesses, congenital abnormalities, neurological disorders and accidental injury.…”
Section: Economic Analysismentioning
confidence: 99%
“…There is good evidence from various sources that the rate of all-cause mortality is higher in individuals with ID, 63,279,282 particularly due to excess deaths from respiratory disorders, neurological diseases, congenital abnormalities and accidents. Standardised mortality ratios (SMRs) of 2.28 (95% CI 2.02 to 2.56) for men with ID and 3.24 (95% CI 2.83 to 3.69) for women with ID, compared with the general population, reported in a 14-year study of individuals from the Leicester area 279 were applied to the other-cause mortality rates that were derived from the ONS data.…”
Section: Cancer Mortalitymentioning
confidence: 99%
See 3 more Smart Citations